Digital Technologies in Litigation vs Digital Human Rights - Ostafiichuk, Liudmyla (Lumen Publishing House, 2020)
The article is devoted to the study of human rights in terms of data available to an indefinite number of persons in the electronic services of the site Judiciary of Ukraine. It is established that along with the availability of the Internet the protection of fundamental human rights should be developed in any information environment. It is proved that the possibility of litigation online is combined not only with the availability of the Internet of a person - a participant in the process but also the current technical inability of a significant number of courts to onduct high-quality court hearings. The main obstacle is the poor quality of communication infrastructure and the lack of knowledge and skills of using digital technologies of the majority of the population. These obstacles must be removed by the State which has a duty to provide the basis for the dignified treatment of every member of society. It has been found that the openness of court decisions affects access to justice and does not promote respect for the rights of individuals to the confidentiality of personal data private and family life. It is substantiated that the indefinite storage of electronic copies of court decisions violates the human right to be forgotten. In order to overcome the identified gaps in the regulation of the use of digital technologies in the judiciary it was concluded that a clear regulatory environment should be created to achieve a balance of interests of the state and society and protect fundamental human rights in the digital age because the essence of man and changes.
Keywords: Court; Digital Technology; Human Rights; Digital Human Rights